Haemophilus influenzae type b serology in childhood leukaemia: A case–control study - Groves, F D (Nature Publishing Group, 2001)
Antibody to Haemophilus influenzae type b (Hib) polysaccharide (PRP) was measured in 42 children with acute lymphoblastic leukaemia (ALL) and 42 non-leukaemic hospital controls. Modelling anti-PRP concentrations as a function of age revealed that the slopes of the trend lines differed significantly between cases and controls (P = 0.05); anti-PRP concentrations were lower among younger cases, and higher among older cases, than among controls of the same ages. © 2001 Cancer Research Campaign http://www.bjcancer.com